2015
DOI: 10.1128/aem.02246-14
|View full text |Cite
|
Sign up to set email alerts
|

Use of Adaptive Laboratory Evolution To Discover Key Mutations Enabling Rapid Growth of Escherichia coli K-12 MG1655 on Glucose Minimal Medium

Abstract: Adaptive laboratory evolution (ALE) has emerged as an effective tool for scientific discovery and addressing biotechnological needs. Much of ALE's utility is derived from reproducibly obtained fitness increases. Identifying causal genetic changes and their combinatorial effects is challenging and time-consuming. Understanding how these genetic changes enable increased fitness can be difficult. A series of approaches that address these challenges was developed and demonstrated using Escherichia coli K-12 MG1655… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
319
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(346 citation statements)
references
References 61 publications
20
319
0
Order By: Relevance
“…S. aureus is known to have a complicated gene regulatory structure that may inhibit its growth on minimal media, despite the presence of biosynthetic pathways for these metabolites (12,14). Longer-term growth or training in the laboratory for these strains may allow for eventual growth in the minimal medium defined here (35).…”
Section: Known S Aureus Virulence Factors Are Unequally Distributed mentioning
confidence: 99%
“…S. aureus is known to have a complicated gene regulatory structure that may inhibit its growth on minimal media, despite the presence of biosynthetic pathways for these metabolites (12,14). Longer-term growth or training in the laboratory for these strains may allow for eventual growth in the minimal medium defined here (35).…”
Section: Known S Aureus Virulence Factors Are Unequally Distributed mentioning
confidence: 99%
“…A spline was fit to the growth rate of each experiment, and significant increases in growth rates were identified as discussed previously (7). The resulting jumps in growth rates showed that the plateaus in growth occurred at specific values ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Automation was utilized here and in previous studies (4,7,41). Manual processes are often hampered by researcher availability, whereas machines can measure and passage cells around the clock; for example, approximately 5 to 7 passages per day were performed in automated studies (4,7,41), compared to 1 or 2 passages per day in manual studies (14,15,18).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations